2007
DOI: 10.1111/j.1365-2362.2007.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function to estimate the bleeding risk in autoimmune thrombocytopenia

Abstract: Platelet adhesion correlates with bleeding symptoms, while the size of aggregates that are formed under high shear correlates with in vivo platelet activation. The determination of these parameters may assist in estimating an individual bleeding risk and thus a decision for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…In contrast, we report that increased levels of P-selectin on the surface of unstimulated platelets and reduced TRAP-induced platelet activation in ITP patients are significantly associated with higher bleeding scores even after adjustment for platelet counts (Figure 3; supplemental Table 2). A likely explanation for the difference in findings is that we used whole blood flow cytometry to study platelet activation whereas Panzer et al 6,29 performed flow cytometric analysis on platelet-rich plasma, the preparation of which is prone to introduce artifactual platelet activation. 8 In a recent study, 7 van Bladel et al reported that pediatric chronic ITP patients with a severe bleeding phenotype demonstrated decreased platelet co-aggregation with normal donor platelets in response to phorbol myristate acetate, compared with patients with a mild bleeding phenotype.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, we report that increased levels of P-selectin on the surface of unstimulated platelets and reduced TRAP-induced platelet activation in ITP patients are significantly associated with higher bleeding scores even after adjustment for platelet counts (Figure 3; supplemental Table 2). A likely explanation for the difference in findings is that we used whole blood flow cytometry to study platelet activation whereas Panzer et al 6,29 performed flow cytometric analysis on platelet-rich plasma, the preparation of which is prone to introduce artifactual platelet activation. 8 In a recent study, 7 van Bladel et al reported that pediatric chronic ITP patients with a severe bleeding phenotype demonstrated decreased platelet co-aggregation with normal donor platelets in response to phorbol myristate acetate, compared with patients with a mild bleeding phenotype.…”
Section: Discussionmentioning
confidence: 98%
“…27 Panzer et al reported an increased percentage of circulating P-selectin-positive platelets in adult chronic ITP patients 28 and that ITP patients with high platelet surface P-selectin in vivo showed reduced agonist-induced platelet activation. 29 Panzer et al subsequently reported 6 that P-selectin expression on circulating platelets of ITP patients did not correlate with bleeding score, whereas platelet count and von Willebrand factordependent platelet adhesion were inversely associated with bleeding score. In contrast, we report that increased levels of P-selectin on the surface of unstimulated platelets and reduced TRAP-induced platelet activation in ITP patients are significantly associated with higher bleeding scores even after adjustment for platelet counts (Figure 3; supplemental Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Further, agonist inducible platelet activation has been shown to be negatively associated with both platelet counts and spontaneous platelet activation. 2 Recently, pediatric ITP patients with lower agonist inducible platelet activity were shown to have more severe bleeding than pediatric ITP patients with higher platelet activity and this association persisted after correction for platelet counts.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of an activity with higher risk of trauma, such as contact sports, should not be considered low risk. In patients with unexpected bleeding, additional laboratory tests should be performed to identify platelet dysfunction [20] or an additional haemostatic abnormality e.g. underlying von Willebrand disease [21,22].…”
Section: Introductionmentioning
confidence: 99%